Cognitive aptitudes and strategies of sequential memorization of pupils in a private school in Comas - García P., Pedro (2009)
In the current moment it is insisted on considering to be the importance of the critical period of the development of the child, referring to the whole influence of the social, educational and familiar conditions during the whole process of training, which in turn allow the acquisition and develop so much of cognitive, affective processes, since as conative-motivational and in general lines of your personality as an everything. The studies of the memorization, for treating itself about a cognitive indispensable process in the learning, which allows the storage and update of the information, are and they will be always of great transcendency. Likewise independently of the strategy of memorization that is in use, this one I try help to constructing the cognitive aptitudes in every stage of cognitive development of the child. An opportune evaluation so much of the strategies of memorization, since as of the aptitudes, allows us the later detection of problems of school learning, be these of global or specific nature. Of there that in this study it tries to describe and to explain like are the most frequent strategies of memorization in the children from 6 to 11 years that they contribute favourably or inadequately in the structure of the component intellective, or of the cognitive aptitudes in the childhood.